2020
DOI: 10.3389/fams.2020.564935
|View full text |Cite
|
Sign up to set email alerts
|

From Learning Gait Signatures of Many Individuals to Reconstructing Gait Dynamics of One Single Individual

Abstract: Based on the same databases, we computationally address two seemingly highly related, in fact drastically distinct, questions via computational data-driven algorithms: 1) how to precisely achieve the big task of differentiating gait signatures of many individuals and 2) how to reconstruct an individual's complex gait dynamics in full. Our brains can "effortlessly" resolve the first question, but will definitely fail in the second one because many fine temporal scale gait patterns surely escape our eyes. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…That is, too many interacting relational patterns are likely resulted because computed foot-specific states are varying in their durations. This phenomenon was shown and concluded in an experiment in [10] via Lempel-Ziv complexity evaluations.…”
Section: A Data Visualizations and Representations Of Gait Rhythmic T...mentioning
confidence: 60%
See 3 more Smart Citations
“…That is, too many interacting relational patterns are likely resulted because computed foot-specific states are varying in their durations. This phenomenon was shown and concluded in an experiment in [10] via Lempel-Ziv complexity evaluations.…”
Section: A Data Visualizations and Representations Of Gait Rhythmic T...mentioning
confidence: 60%
“…Discovering such a personal collection of biomechanical states is a computing task that has not been well established in literature yet. In our previous study [10], we reported findings of alternating cyclic states. Such data-driven cluster-based states' variations are too big to be biomechanically coherent.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations